Current Status of Treatment Adherence Among Outpatient Osteoporosis Patients at the University of Medicine and Pharmacy Hospital, Vietnam National University, Hanoi - Thi Thuy, Dang; Thi Hang, Le; Ba Tam, Nguyen; Thi Ly, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences; Acticle in Press, 2026)
Abstract: Objective: To describe treatment adherence and analyze associated factors among outpatients with osteoporosis at the University of Medicine and Pharmacy Hospital, Vietnam National University, Hanoi, in 2025. Methods: An analytical cross-sectional study was conducted on 196 outpatients with osteoporosis who had received treatment for at least 3 months. Participants were recruited consecutively. Data were collected through face-to-face interviews using a structured questionnaire adapted from Phan Thi Thuy (2018) and analyzed with SPSS 22.0 using descriptive statistics, chi-square/Fisher’s exact tests, and univariate logistic regression to estimate odds ratios with 95% confidence intervals. Results: Women accounted for 83.7% of participants; mean age was 62.3 ± 8.0 years and mean BMI was 23.0 ± 2.9 kg/m². Adequate knowledge was observed in 92.9% of patients, and overall treatment adherence reached 89.8%. Adherence to selected behaviors was 91.8% for dietary compliance according to health-care guidance, 93.9% for regular physical activity under sunlight, 91.8% for fall-prevention practices, 96.4% for taking the correct medication and dose, and 93.4% for regular follow-up visits. Age, educational level, economic status, family support, and knowledge were significantly associated with adherence. Adequate knowledge was strongly associated with adherence (OR = 18.89; 95% CI: 5.64-63.32), as was family support (OR = 5.47; 95% CI: 1.87-15.94). Conclusion: Treatment adherence among outpatients with osteoporosis was relatively high. Targeted health education, reminder systems for follow-up visits, and stronger family engagement should be promoted to sustain long-term adherence. Keywords: Osteoporosis; treatment adherence; outpatients; associated factors; health education.